Interconnection of representations with gender issues in teaching - Rabelo, Amanda Oliveira (2019)
In order to understand how «gendered» male and female teachers think, we will study the general concepts of representation by analyzing the production and processing of these concepts, because representations outspread by society carry prejudice and categorizations that are, somehow, embodied by teachers. Therefore, we need to know how representations can be absorbed, denied or shared. Accordingly, we have performed a literature review on publications about representations based on many approaches, which were divided into two blocks of analysis: conceptualization of social representations and complex representations. The analysis showed that based on common sense a common way, but these factors bring along peculiar practices of each individual or teacher that are loaded with their ways of thinking.